Dampak Pandemi Covid-19 terhadap Pasar Modal di Indonesia - Dedi Junaedi; Faisal Salistia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2020)
This study aims to: (1) examine the influence of a pandemic on the development of the stock market (CSPI) in Indonesia; (2) analyzing the effect of externalities on the dynamics of stock market developments in Indonesia; and (3) examine whether differences in social distancing policies affect the dynamics of Indonesian capital market movements. The research method uses quantitative analysis with a dummy variable multiple regression approach. JCI as a bound variable, while the independent variable is the number of Covid-19 pandemic cases in Indonesia, China and Spain, then the movement of the FTSE100 stock indexes (London), Hangseng (Hong Kong) and NASDAQ (New York), as well as differences in social distancing policies in Indonesia (Indonesia) Task Force, WFH and PSBB). The results of the study concluded: The movement of the composite stock index (CSPI) on the Jakarta Stock Exchange is influenced by internal and external conditions. Internally the condition of the Covid-19 pandemic and social distancing (WFH and PSBB) policies in the country have influenced the dynamics of the stock market (indicated by the movement of the IHSG index on the JSX). Externally, the Covid-19 pandemic in China and Spain also influenced the dynamics of the stock market in Indonesia (IHSG index). Likewise, the dynamics of the stock market in Hong Kong (Hangseng), London (FTSE100) and News York (NASDAQ). The coronavirus pandemic in Indonesia, China, the dynamics of the Nasdaq stock market in New York, and the social dintancing (WFH and PSBB) policies had a negative impact on the movement of the JCI stock index. While the pandemic in Spain, the dynamics of the stock market in Hong Kong (Hangseng) and London (FTSE100) actually had a positive impact on stock market conditions in Indonesia (JSX).